Rantai Pasok Kentang Di Desa Makaaruyen Kecamatan Modoinding Kabupaten Minahasa Selatan - Mumu, Glaydies Inggrid; Pakasi, Caroline Betsi Diana; Mandei, Juliana Ruth (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine product flow, information flow, and financial flow of potato commodities in Makaaruyen Village, Modoinding District, South Minahasa Regency. This research was conducted for 8 months, from March to October 2022. The data analysis method used in this research is descriptive analysis using tables and charts. The data used are primary data and secondary data. Primary data was obtained through direct interviews with respondents using a structured questionnaire. Secondary data were obtained from offices, districts, village offices, related agencies and journals relevant to research. The results showed that the potato supply chain in Makaaruyen Village consisted of farmers, collectors, traders and retailers. The flow of potato products starts from farmers who produce potatoes, collectors who buy potatoes from farmers, then retail traders who sell potatoes to end consumers and there are inter-island traders. The price level in the product flow varies in each supply chain actor. The financial flow starts from retailers who buy potatoes to collectors, then collectors buy potatoes from farmers with a payment system made entirely in cash. The flow of information flows from two directions, the first direction is that farmers inform collectors about the products harvested, collector traders inform inter-island traders and also inform retailers about the number of requests to farmers. The second stream of collecting traders informs farmers about the volume of crabs requested, the purchase price, the time to return the product and information about the supply of the product.